A Comparative Study between Karydakis Flap Reconstruction and Double Z-Plasty in Patients with Sacrococcygeal Pilonidal Disease. (7th September 2014) - Kayal, Ankit; Hussain, Akhlak; Choudhary, Anil; Meghwal, Ashok
Abstract : The most difficult problems that follow surgery for pilonidal disease are persistent unhealed midline wound and recurrence. Various innovations were proposed to deal with these problems. The adipocutaneous flap of Karydakis was devised to shift the natal cleft, while Z-plasty involves fasciocutaneous flap. The present prospective randomized trial was conducted on 50 cases of symptomatic or recurrent pilonidal sinuses divided randomly into two equal groups undergoing Karydakis procedure and Z-plasty. The duration of hospitalization for Karydakis procedure was found significantly lesser than that for double Z-plasty (P < 0.001 ). Similar observations are obtained for duration of wound healing (P < 0.001 ), work off period (P < 0.001 ), and the duration of presence of significant pain postoperatively (P < 0.001 ). The overall complications were more in double Z-plasty. Recurrence developed in 32% of the cases in double Z-plasty group comparable to no recurrence seen in Karydakis procedure. Thus, Karydakis flap was found superior to double Z-plasty having less seroma formation, no local hematoma, and no flap necrosis. Statistically, this comparison was highly significant (P < 0.001 ). Karydakis flap has some added advantages over double Z-plasty technique like keeping scar away from the midline and flattening of the natal cleft, thus reducing local recurrence rates.